1996
DOI: 10.1093/oxfordjournals.esr.a018179
|View full text |Cite
|
Sign up to set email alerts
|

'Losing my religion'1: a dynamic analysis of leaving the church in the Netherlands

Abstract: In this article, we examine the influence of individual attributes (education, parental education, religious homogamy of parents, religious homogamy of respondent and spouse, frequency of attending religious services, and denomination) and contextual characteristics (cohort and period effects of secularization) on the risk of leaving a faith, using life-event data from the Dutch Family Survey 1992-1993. This approach allows a stronger test of the direction of causality, and enables us to disentangle life-cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
83
1
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(94 citation statements)
references
References 8 publications
5
83
1
5
Order By: Relevance
“…Differences in values, ideas and beliefs between individuals is in other words caused by integration into different social groups in society. This theory has been applied successfully to religious groups: people conform to the religiosity of the social group in which they are integrated (Need and De Graaf, 1996). Among immigrants, previous studies have shown that immigrants also conform to levels of religiosity in the host society and that more integrated migrants conform even more to ethnic majority religiosity (Van Tubergen, 2006;The authors, 2013).…”
Section: Ethnic School Segregationmentioning
confidence: 99%
“…Differences in values, ideas and beliefs between individuals is in other words caused by integration into different social groups in society. This theory has been applied successfully to religious groups: people conform to the religiosity of the social group in which they are integrated (Need and De Graaf, 1996). Among immigrants, previous studies have shown that immigrants also conform to levels of religiosity in the host society and that more integrated migrants conform even more to ethnic majority religiosity (Van Tubergen, 2006;The authors, 2013).…”
Section: Ethnic School Segregationmentioning
confidence: 99%
“…Volunteering is strongly related to religious involvement as well as the level of education, both in the USA (Wilson, 2000;Independent Sector, 2002) and in The Netherlands (Bekkers, 2004(Bekkers, , 2005. Because parents transmit religion (Need and De Graaf, 1996;Myers, 1996) as well as education (Blau and Duncan, 1967;Ganzeboom et al, 1991) to their children, it may be that the apparent transmission of volunteering is due to the transmission of religion and education. Any study lacking the level of education and religious involvement as control variables (e.g.…”
Section: Acta Sociologica 50(2)mentioning
confidence: 99%
“…Previous research has used Durkheim's (1951) social integration theory as a general idea from which to derive a series of hypotheses about religion (Need and De Graaf 1996;Te Grotenhuis and Scheepers 2001). Within this perspective it is argued that social settings or groups in which people participate influence their religious beliefs and practices.…”
Section: Social Integration Theorymentioning
confidence: 99%